Community annotation: Procedures, protocols, and supporting tools - Elsik, Christine G.; Worley, Kim C.; Zhang, Lan; Milshina, Natalia V.; Jiang, Huaiyang; Reese, Justin T.; Childs, Kevin L.; Venkatraman, Anand; Dickens, C. Michael; Weinstock, George M.; Gibbs, Richard A. (Genome Research, 2006)
Investigators at the Baylor College of Medicine Human Genome Sequencing Center (BCM–HGSC) and BeeBase organized a community-wide effort to manually annotate the honey bee (Apis mellifera) genome. Although various strategies for manual annotation have been used in the past, the value of dispersed community annotation has not yet been demonstrated. Here we make a case for the merit of dispersed community annotation. We present annotation procedures, standard protocols, and tools used for sequence analysis, data submission, and data management. We also report lessons learned from this dispersed community annotation effort for a metazoan genome.
10.1101/gr.5580606